Determinants of corporate tax non-compliance: evidence from the Special Voluntary Disclosure Programme (SVDP) / Redzuan Ahmad, Zuraeda Ibrahim and Nor Syafinaz Shaffee - Ahmad, Redzuan; Ibrahim, Zuraeda; Shaffee, Nor Syafinaz (2022)
This paper aims to provide empirical evidence on the determinants of corporate tax non-compliance in Malaysia based on secondary data collected during the Special Voluntary Disclosure Programme (SVDP) in 2018 and 2019. A total of 4,192 cases have been extracted from the integrated Case Management System (CMS) and Sistem Taksir Sendiri Syarikat (STSC) systems of the Inland Revenue Board Malaysia (IRBM) and analysed. The tax gap has been used as a proxy for tax non-compliance. The independent variables were corporate characteristics and strategies undertaken by companies for tax non-compliance. The research findings reveal that there is a significant positive relationship between firm size, nationality, real estate, understatement of sales, overstatement of purchases, and other strategies and corporate tax non-compliance. Construction and unallowable expenses have a significant negative relationship with corporate tax non-compliance. This study is the first study that investigates factors that could influence the corporate tax non-compliance based on SVDP data. This dataset is unique as it was extracted during the SVDP programme. The findings support on previous findings and provide further essential information to policymakers and tax authorities in designing tax audit guidelines, planning for tax amnesty initiative in future, providing training for their manpower, and formulating effective enforcement strategies